ANALISIS GANGGUAN DISLEKSIA PADA ANAK USIA DINI DI RA PERWANIDA II PLUMPANG - ASTARIN, WA ODE SYAMZAHRAH; MUTIARA SARI, ANNISA MAWADDAH; SHOFIANA, ZULFA (Universitas Islam Darul Ulum, 2024)
This study aims to be able to analyze and describe written forms of language in a child affected by dyslexic language disorders. Language disorders that can cause problems or obstacles to language development in children can be caused by dyslexia, the disease can also attack the neurological functions of the brain which can certainly affect the development of language processing in a child. This research uses a descriptive qualitative research method, where the main source of research data is obtained from written and oral formations of documentation, from one of the elementary school students domiciled in Babat, Lamongan named SJL (the name mentioning using initials). Retrieval of data in this study using interviews, documentation, and observation. From the results of research and discussions that have been carried out in this study, SJL has several deficiencies in writing problems, from writing letters that are reversed, sequences of letters that are different from normal children, inaccuracy in writing letters in words and other differences.